Ligand directed self-assembly vs. metal ion coordination algorithm—when does the ligand or the metal take control? - Shuvaev, Konstantin V.; Abedin, Tareque S. M.; McClary, Corey A.; Dawe, Louise N.; Collins, Julie L.; Thompson, Laurence K. (Dalton transactions : an international journal of inorganic chemistry, 2009)
Polyfunctional hydrazone ligands with multidentate terminal donor groups offer metal ions many donor choices, and the coordination outcome depends mainly on the identity of the metal ion. Co(ii) and Ni(ii) prefer to adopt largely undistorted, six-coordinate geometries, while Cu(ii) can easily adapt to a variety of coordination situations (e.g. CN 4-6), and will optimize its coordination number and stereochemistry based on all the available donors. Ni(ii) and Co(ii) form simple [2 x 2] [M(4)-(micro(2)-O)(4)] square grids with such ditopic hydrazone ligands, and ignore other coordination options, while Cu(ii) tries to bind to all the available donors, and forms extended and 2D structures based on linked Cu(ii) triads rather than grids. Ni(ii) is also reluctant to compromise its desire to maximize its crystal field stabilization energy (CFSE) by binding to 'weak' ligands, and with a tetratopic pyrazole bis-hydrazone ligand it ignores the oxygen donors in favour of nitrogen, forming a novel trinuclear, triangular cluster. Also, reaction of a linear Ni(ii)(3) complex of a tetratopic pyridazine bis-hydrazone ligand with NiN(6) coordination spheres with Cu(ii), leads exclusively to a square Cu(12) grid based complex, and complete displacement of nickel. Structural and magnetic properties are highlighted, and metal-ligand interactions are discussed in detail.